PENGUJIAN KONSTITUSIONAL UNDANG-UNDANG PENGESAHAN PERJANJIAN INTERNASIONAL - Dian Utami Mas Bakar (Universitas Airlangga, 2014)
This research aims to analyze normatively about the nature of the act of the ratification of international treaties and outlines the act of constitutional review to the ratification of international treaties. The results of research shows: 1) the standing of international treaties is dependent on the scores of international law who espoused a country. Ratification of a treaty embodied through the two phases namely: the phases of the national law and of international law; 2) the meaning of “DPR approval” must be viewed in the context of internal procedures meanwhile ratification must be vied of external procedure. 3) Constitutional review may results in wide and problematic decision. If it is declared void then execution of the decision will face obstacles. If there is a denunciation, Government is in the difficult position and even can trigger dispute to the international Court of Justice.Keywords: ratification, international agreement, legislation